Efficient electrochemical reduction of CO2 to ethanol on Cu nanoparticles decorated on N-doped graphene oxide catalysts. (October 2019) - Yuan, Jing; Yang, Man-Ping; Zhi, Wen-Ya; Wang, Hui; Wang, Huan; Lu, Jia-Xing
Graphical abstract: Various Cu nanoparticles dispersedly load on the sheet-like pyridoxine modification graphene oxide (GO-VB6 -Cu) materials were successfully and systematically synthesized through a simple and facile approach, which reveal superior catalytic activity, i.e. low overpotential (0.140 V) for ethanol formation and high Faradaic efficiency of ethanol with 56.3% at the potential of −0.250 V vs. the reversible hydrogen electrode. This work may shed light on the design and preparation of novel functionalized carbon materials for efficient CO2 electrochemical reduction. Highlights: GO-VB6 -Cu exhibits high activity, selectivity and stability for electroreduction of CO2 . The Cu loading used in GO-VB6 -Cu can lower the EtOH formation overpotential and improve the EtOH formation efficiency. The enhanced activity is attributed to the large ECSA, enhanced CO2 adsorption, and low electron transfer resistance. Abstract: Efficient electrochemical reduction of CO2 to ethanol is a promising approach for obtaining high-density renewable energy storage and relieving environment stress. In this paper, we report the highly efficient electrochemical reduction of CO2 to ethanol by using Cu nanoparticles decorated on pyridoxine modification graphene oxide sheets (GO-VB6 -Cu) as robust electrocatalysts. CO2 was efficiently reduced to ethanol in 0.1 M KHCO3 solution by using GO-VB6 -Cu-2 catalyst at an overpotential as low as 0.140 V. The maximum Faradaic efficiency for ethanol formation of 56.3% was obtained at the potential of −0.250 V vs. the reversible hydrogen electrode. The resultant nanocomposite presented no degradation after approximately 24 h of continuous operation, demonstrating the pronounced stability of the electrode. The notable reactivity toward CO2 reduction achieved here can be ascribed to large electrochemically active surface area, enhanced CO2 adsorption, and low electron transfer resistance.